Methodology to determine product dimensions based on user anthropometric data - Hernandez Arellano, Juan Luis (Springer, 2018)
The determination of product dimensions is usually a complicated task developed during the design process. Typically, product dimensions are developed using wrong percentiles and wrong anthropometric data, i.e., designers use data from other populations. This chapter proposes a method for dimensioning products based on user–product interactions and the user’s anthropometric dimensions. The methodology includes 7 steps: (1) determine the objective of the product, (2) identify the interactions user–product, (3) assign a name to the product dimensions, (4) identify the user dimensions to design the product, (5) determine the percentiles and Z-scores for each product dimension, (6) calculate the per- centiles, (7) determine the dimensions of the product. In order to exemplify the proposed method, two examples were developed using the methodology. The first was related with the design of a conventional bench, and the second was related with design of an adjustable school desk. After applying the proposed method, both products were successfully dimensioned.